2021
DOI: 10.3390/app11052336
|View full text |Cite
|
Sign up to set email alerts
|

Debris Flow Characteristics in Flume Experiments Considering Berm Installation

Abstract: This study was conducted to identify the characteristics and mobility of debris flows and analyze the performance of a berm as a debris flow mitigation measure. The debris flow velocity, flow depth, Froude number, flow resistance coefficients, and mobility ratio were accordingly determined using the results of flume tests. To analyze the influence of the berm, the results for a straight channel test without a berm were compared with those for a single-berm channel test. The debris flow velocity was observed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…It was evident that the distribution of sediment deposition in terms of total volume was influenced by the inclination of the flume and indicated that when θ d is increased, there is a clear correlation with a decrease in the volume of deposits present on the board. In a study conducted by [39], the experimental findings provided support for the idea that as the channel slope, which represents the flume inclination, increased, the total travel distance of debris flow also increased. Aside from flume inclination, fluid volume also showed a significant association with V T (r = −0.260, p < 0.05), V out (r = 0.783, p < 0.01), P A (r = −0.210, p < 0.05), S A (r = −0.210, p < 0.05), Ψ (r = −0.285, p < 0.05), H p (r = 0.107, p < 0.05), and P B (r = −0.210, p < 0.05).…”
Section: Discussionmentioning
confidence: 80%
“…It was evident that the distribution of sediment deposition in terms of total volume was influenced by the inclination of the flume and indicated that when θ d is increased, there is a clear correlation with a decrease in the volume of deposits present on the board. In a study conducted by [39], the experimental findings provided support for the idea that as the channel slope, which represents the flume inclination, increased, the total travel distance of debris flow also increased. Aside from flume inclination, fluid volume also showed a significant association with V T (r = −0.260, p < 0.05), V out (r = 0.783, p < 0.01), P A (r = −0.210, p < 0.05), S A (r = −0.210, p < 0.05), Ψ (r = −0.285, p < 0.05), H p (r = 0.107, p < 0.05), and P B (r = −0.210, p < 0.05).…”
Section: Discussionmentioning
confidence: 80%
“…In the upper reaches of the Jinsha River, there are 32 debris flow gullies between the engineering area of the Benzilan Hydropower Station and that of the Xulong Hydropower Station alone, posing a substantial threat to construction and operation of existing and planned hydropower Water 2023, 15, 2072 2 of 17 projects [2]. Therefore, predicting the run-out process and extent of debris flow is important for disaster prevention and mitigation for hydropower projects in the deep-cutting canyon area of Southeast Tibet [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%